The Development of Africa Issues, Diagnoses and Prognoses (Social Indicators Research Series,, 2018)
This volume analyses many of the real development challenges confronting the African continent, presenting fresh and current objective examinations, narratives, interpretations and pathways to the continent's development. It interrogates and answers established, critical, current and pragmatic problems confronting Africa today, and provides workable pathways out of the development problems, so that scholarship, policy and practice will be positively impacted. This volume adds great depth and extended breadth to the knowledge base on development of Africa. It provides excellent resources for academics, scholars, student, policy makers and all those interested in issues affecting Africa's development.